MEDICAL, LEGAL, AND SOCIAL ASPECTS OF THE SURROGATE MOTHER PHENOMENON - himmaturojuli Rosyid Ridlo; Reisca Tiara Hardiyani (Journal Philosophy of Law, 2022)
Uterine rental (Surrogate Mother) is where a woman makes a gestational agreement with a husband and wife. The surrogate mother is willing to bear the seeds of a married couple by receiving certain rewards. Uterine rental occurs because the wife can not conceive because of something that happened to her womb. This study uses normative law research methods using normative case studies in the form of legal behavior products by reviewing Law No. 36 of 2009 concerning Health, Government Regulation (PP) No. 61 of 2014 concerning Reproductive Health, the Civil Code, and Law No. 1 of 1974 concerning Marriage. The results of this study are 1. Uterine rental is a pregnancy outside the natural way that can only be done to married couples bound by a legal marriage and experience infertility or infertility to produce offspring 2. All forms of surrogate mother agreements in Indonesia are null and void because they contradict the existing laws and regulations. 3. A child born to a Surrogate Mother who is bound in marriage is the legal child of the woman and her husband, but if the child is born to a Surrogate Mother who is not bound by marriage, the child will be the illegitimate child of the woman. 4. Inheritance rights of children born to surrogate mothers who are bound in marriage will receive inheritance rights from the surrogate mother and her husband. If the surrogate mother is not bound by marriage, the child will only receive inheritance rights from the surrogate mother.